2016
DOI: 10.21273/hortsci.51.5.543
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Content in ‘Passe-Crassane’ Winter Pear as Affected by 1-Methylcyclopropene during Cold Storage and Shelf Life

Abstract: ‘Passe-Crassane’ is a winter pear which requires a cold storage period to produce ethylene and properly ripen. In this study, the effects of 1-methylcyclopropene (1-MCP), an ethylene perception inhibitor, were studied during cold storage (30, 60, 90, and 135 days) and shelf life at 20 °C (30 days) of ‘Passe-Crassane’ pears. Ethylene accumulation was monitored and quality parameters were measured. Oxidative stress of fruit was estimated by measuring lipid peroxidation. The cell antioxidant status was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Franck et al (2003) noticed that browning inducing CA storage conditions in 'Conference' pear resulted in more than 4-fold faster decrease in ascorbic acid concentration. Cocetta, Mignani, and Spinardi (2016) found that treatment of 'Passe Crassane' pear with 400 nL L -1 1-MCP maintained a higher ascorbic acid during air storage at 0 °C and during shelf life. The effect of 1-MCP on pear seems to be similar to apple.…”
Section: Quality Attributes Of 'Alexander Lucas' Pearmentioning
confidence: 90%
“…Franck et al (2003) noticed that browning inducing CA storage conditions in 'Conference' pear resulted in more than 4-fold faster decrease in ascorbic acid concentration. Cocetta, Mignani, and Spinardi (2016) found that treatment of 'Passe Crassane' pear with 400 nL L -1 1-MCP maintained a higher ascorbic acid during air storage at 0 °C and during shelf life. The effect of 1-MCP on pear seems to be similar to apple.…”
Section: Quality Attributes Of 'Alexander Lucas' Pearmentioning
confidence: 90%
“…Also, selenium treatments were effective in repressing the expression of ET biosynthetic genes, and in stimulating the enzymatic antioxidant systems in tomato, while prolonging the shelf life ( Zhu et al., 2017 ). Another widely used product, 1-MCP can have different effects on the quality attributes of climacteric fruits like tomatoes ( Poyesh et al., 2018 ; Zou et al., 2018 ; Taye et al., 2019 ) pears ( Cocetta et al., 2016 ), apples ( Kim et al., 2018 ) and bananas ( Satekge and Magwaza, 2020 ). On the other hand, it has been reported to have just slight effects on internal fruit quality of non-climacteric fruits ( Li et al., 2016 ).…”
Section: The Role Of Ethylene In Postharvest Quality Of Fresh and Fre...mentioning
confidence: 99%